Respuesta :
[tex]-( \frac{-6}{7} )* (\frac{6}{7}) [/tex]
Remove parentheses : (a) = a
[tex] \frac{6}{7} * \frac{6}{7} [/tex]
Apply exponent rule : [tex]a^b.a^c = a^{b+c} [/tex]
[tex] \frac{6}{7} * \frac{6}{7} = ( \frac{6}{7}) ^{1+1} = (\frac{6}{7} )^{2} [/tex]
Apply exponent rule:
[tex] (\frac{a}{b})^c = \frac{a^c}{b^c} [/tex]
[tex] \frac{6^2}{7^2} = \frac{36}{49} [/tex]
hope this helps!.
Remove parentheses : (a) = a
[tex] \frac{6}{7} * \frac{6}{7} [/tex]
Apply exponent rule : [tex]a^b.a^c = a^{b+c} [/tex]
[tex] \frac{6}{7} * \frac{6}{7} = ( \frac{6}{7}) ^{1+1} = (\frac{6}{7} )^{2} [/tex]
Apply exponent rule:
[tex] (\frac{a}{b})^c = \frac{a^c}{b^c} [/tex]
[tex] \frac{6^2}{7^2} = \frac{36}{49} [/tex]
hope this helps!.